(untitled) (Eurasian Medical Research Periodical, 2023)
The relevance of today’s research in the world is based on the high risk of recurrence of chronic rhinosinusitis. The treatment of rhinosinusitis remains relevant and has a difficult solution in the field of Otorhinolaryngology even today. Among LOR diseases, it occurs in between 5% and 15% of patients. As before, in connection with the deterioration of the ecological condition, side effects of the external environment and harmful factors of production, a recurrence of the disease and a high incidence rate remain. Currently, rhinosinusitis is considered as a polyethiological disease, on the basis of which infectious allergic inflammation and disorders of the allergic state of the body, autoimmune processes, Genetic Disorders at the chromosome level and functional disorders of the vegetative nervous system lie. These processes lead to a decrease in the overall reactivity of the body and local immunity of the nasal mucosa, and are also the result of impaired metabolism and microcirculation, hypoxia and endogenous intoxication